A novel null HLA‐B allele, B*15:375N, due to a seven base pair deletion within exon 3. (4th January 2016) - Planelles, D.; Balas, A.; Muñoz, C.; Puig, N.; Vicario, J. L.
Abstract: Characterization of a novel HLA‐B null allele, B*15:375N, with a seven base pair deletion in exon 3.